Distal deep vein thrombosis as a presenting manifestation of tropical hyper-eosinophilia - Sharma, Vishnu; Bagrodia, Vansh; Digwal, Arpita; Parchwani, Tanishk (International Journal of Research in Medical Sciences, 2024)
A young woman with swelling and pain in her left leg was diagnosed with deep vein thrombosis (DVT) confirmed by Doppler study. However, she also had hypereosinophilia (HE), which led to investigations for possible underlying causes. Positive serologic testing for Filariasis suggested it as the likely cause, highlighting DVT as a presenting manifestation of tropical HE. Treatment with rivaroxaban for DVT and antiparasitic medication led to normalization of eosinophil counts and complete resolution of DVT on follow-up. This case presents a rare occurrence of DVT seen as a presentation with tropical HE.